2007
DOI: 10.3346/jkms.2007.22.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Twin-to-twin Delivery Interval and Umbilical Artery Acid-base Status in the Second Twin

Abstract: The purpose of this study was to determine the effect of twin-to-twin delivery interval on umbilical artery acid-base status of the second twin at birth. This was a retrospective cohort study of all live-born twins with measured acid-base status in umbilical arterial blood who were delivered after 34 weeks' gestation from June 2003 to February 2006. Twins with any maternal or fetal complications were excluded. Subjects were divided into two groups based on the mode of delivery of the first twin: normal cephali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
(27 reference statements)
4
9
2
3
Order By: Relevance
“…It has been proposed that the TTDT should be less than 15 minutes and certainly not more than 30 minutes (MacLennan AH, 1994). Similarly, other authors suggest that fetal acidemia may develop when the TTDT exceeds 20 minutes (Suh et al, 2007). These observations have been supported by another cohort study that found a higher risk of metabolic acidosis of the second twin after a TTDT of more than 60 minutes (Edris et al, 2006).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…It has been proposed that the TTDT should be less than 15 minutes and certainly not more than 30 minutes (MacLennan AH, 1994). Similarly, other authors suggest that fetal acidemia may develop when the TTDT exceeds 20 minutes (Suh et al, 2007). These observations have been supported by another cohort study that found a higher risk of metabolic acidosis of the second twin after a TTDT of more than 60 minutes (Edris et al, 2006).…”
Section: Discussionsupporting
confidence: 74%
“…E-mail: susanne. schneuber@medunigraz.at should be delivered within 15-30 minutes of the first twin (Edris et al, 2006;Erdemoglu et al, 2003;Hartley & Hitti, 2005;Leung et al, 2004;MacLennan, 1994;McGrail & Bryant, 2005;Stein et al, 2008;Suh et al, 2007); other studies concluded that the TTDT is of minor importance. (Bartnicki et al, 1992;Briese et al, 1994;Rayburn et al, 1984;Rydström & Ingemarsson, 1990) The present study investigated the relationship between TTDT and neonatal outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto a estudios previamente publicados con un objeto similar de estudio, algunos autores concluyen que el pH del segundo gemelo es más bajo que el del primero (1,3,7,11-16) y parece deteriorarse con más rapidez (17), también describen una correlación negativa entre el intervalo de nacimiento entre gemelos y las diferencias en el pH de ambos gemelos o el valor del pH de cordón del segundo (11,(17)(18)(19)(20). Sin embargo, no tienen en consideración el estado ácido-base del primer gemelo, ni el deterioro del pH de cordón umbilical del segundo gemelo respecto al primero.…”
Section: Discussionunclassified
“…(8,12,20,38) Abnormal (non-cephalic) presentation (7) and the vaginal route of delivery have been described as risk factors for birth asphyxia. (12,21) Apgar scores < 7 at 1 and 5 mins have been found in 13%-32% and 2%-12% of twins, respectively, (9,19) just as active resuscitation measures are said to be required in nearly 30% of twins. (9) In our study, the incidence of low Apgar scores (score < 7) at 1 min and 5 mins of life was around 8% and 4%, respectively.…”
Section: Discussionmentioning
confidence: 99%